The house on Mango Street - Cisneros, Sandra (New York : Vintage Contemporaries, 1991)
A young girl living in a Hispanic neighborhood in Chicago ponders the advantages and disadvantages of her environment and evaluates her relationships with family and friends.
Wilson's Fiction.
Wilson's Junior High School.
Wilson's Senior High School.
Adult
Keywords: Girls -- Illinois -- Chicago -- Fiction; Hispanic Americans -- Illinois -- Chicago -- Fiction; Bildungsromans; Girls -- Chicago (Ill.) -- Fiction; Hispanic Americans -- Fiction; Chicago (Ill.) -- Fiction; Chicago (Ill.) -- Fiction; Bildungsromane